Determination of the radial position of zero density for profile reflectometry on experimental advanced superconducting tokamak. (1st January 2023) - Zhang, J.; Liu, A.D.; Zhou, C.; Zhuang, G.; Ding, W.X.; Hu, G.H.; Xu, G.S.; Ding, B.J.; Li, M.H.; Zou, X.L.; Zhang, S.B.; Hu, L.Q.; et al.
Abstract: The Experimental Advanced Superconducting Tokamak (EAST) reflectometry is a Frequency-Modulated Continuous-Wave monostatic system with the transmission lines similar to the ITER reflectometer design. One of the most significant and common problems for reflectometry to reconstruct the density profile is the determination of initialization, i.e. zero density position ( R start ), which could be determined by the extraordinary mode (X-mode) reflectometry. The main source of noise still comes from the wave scattering of plasmas despite the sweeping period of around 10 microseconds. It is found that to reduce the random noise of R start, averaging on 25 periods is the optimal solution. During the L-mode discharges with only lower hybrid wave (LHW) heating, R start would move outwards and its fluctuation and the high frequency components of turbulence around R start would be obviously increased when the 2.45 GHz system is switched on, while no obvious change is observed in the 4.6 GHz case. These phenomena are consistent with that 2.45 GHz LHW has less current drive ability than 4.6 GHz LHW on EAST. During ELMy H-mode, the peak of R start is consistent with Deuterium signal and the maximum displacement is about 3 cm. The comparison of density profiles from reflectometry and Lithium beam emission spectroscopy (Li-BES) suggests that setting the density at R start to (4 ± 2)× 10 17 m -3 is much better than zero, while this value is somewhat empirical and closely related to the amplitude threshold for determining the first probing frequency corresponding to R start .